Identification and Abundance of Microplastic Species in Three Final Processing Sites in Lampung Province - Lika Dini Almayda; Marlina Kamelia; Ade Lenty Hoya (Universitas Syiah Kuala, 2025)
Microplastics are plastic waste that is smaller than 5 mm in size Microplastics have persistent properties and contain toxic or carcinogenic chemicals that can seep into the soil through osmosis and enter the food chain, thus impacting health and the environment. The purpose of this study is to determine the types of microplastics in the Three Final Processing Sites in Lampung Province and to determine the abundance of microplastics in the Three Final Processing Sites in Lampung Province. Soil samples were taken using purposive sampling at three different points at the landfill on December 4, 2024. visual identification and abundance of microplastics using microscope and FTIR (Fourier transform infrared) test. The highest abundance of microplastics was found at the Bumi Ayu landfill point (580 particles. Kg-1). The diversity of microplastic characteristics in the form of fragments, fibers, and films, the most fragment particles in soil samples. The color of microplastic particles is predominantly black and brown. The size range of microplastic particles found is between 2,12m-110,25m. Microplastic pollutants are Nylon, PVA, PMMA. The results of this study reveal that plastics that have undergone physical or chemical degradation can more easily become small fragments, thus increasing the number of microplastics produced.